Navigating Platform Dependence: Strategic Decision-Making Process Behind PT Local’s D2C Business Model Shift - Sisca Melinda; Pri Hermawan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
PT Local faces challenges as its heavy reliance on marketplaces begins to limit the company's ability to manage profit margins, access customer data, and build long-term relationships with its own consumers. This situation creates a need to re-evaluate its growth strategy and consider a shift towards a Direct-to-Consumer (D2C) model as an effort to strengthen business autonomy and sustainability. This study aims to explore this transition process by examining the company's internal dynamics and customer responses to the change in sales channels. A qualitative approach was employed through interviews with the internal team, customer surveys, and financial data analysis, supported by the use of the SWOT, TOWS, Porter’s Five Forces, and Resource-Based View (RBV) frameworks to comprehensively understand the company's strategic position. The findings identify five key steps: maintaining marketplaces as an acquisition channel while migrating repeat customers to D2C platforms; enhancing the quality of the D2C experience through more intuitive interface design, faster payment processing, responsive customer service, and reliable delivery; leveraging customer data to build a cross-brand loyalty ecosystem; refining operational and financial system integration; and establishing a cross-functional committee to ensure consistent strategy execution. This study concludes that the transition to D2C is not intended to abandon marketplaces entirely, but rather to reduce dependency by strengthening customer relationships and improving long-term profit stability.